EFFECT OF DNA METHYLATION ON GENOME FUNCTION - Łukasik, Marcin; Karmalska, Jolanta; Szutowski, Mirosław M.; Łukaszkiewicz, Jacek (Prospects in Pharmaceutical Sciences, 2009)
In biochemistry, methylation refers to the replacement of a hydrogen atom with a methyl group. DNA methylation is a type of chemical modification of DNA that can be inherited and subsequently removed without changing the original DNA sequence. It has been demonstrated that DNA methylation is involved in a number of biological processes such as parental imprinting, X chromosome inactivation, and development of tumors. In this article, the present knowledge on the methylation process is reviewed.